Are precious metals and equities immune to monetary and fiscal policy uncertainties?. (December 2021) - Shah, Adil Ahmad; Dar, Arif Billah; Bhanumurthy, N.R.
Abstract: We examine spillovers among policy uncertainties (Monetary and Fiscal), precious metals, and equity markets to investigate whether precious metals and equities are immune to monetary and fiscal policy uncertainties? The monthly data of monetary and fiscal policy uncertainties, gold, silver, and S&P-500 prices from January 1987 to November 2020 are used. The empirical results reveal that the overall spillovers among the system variables are weak. Further, the cross-spillovers between precious metals and policy uncertainties are found to be lower than the cross-spillovers between equity and policy uncertainties. The decomposition of overall spillovers into various frequencies indicate that shorter followed by longer and medium time-horizons drive overall spillovers. The frequency-based results reveal that cross-spillovers between policy uncertainties and equity are mostly driven by shorter horizons. Whereas, the cross-spillovers between policy uncertainties and precious metals are driven by longer horizons. Thus, it appears that precious metals are relatively more immune to the shocks from policy uncertainties than equity markets, thereby suggesting safe investment opportunities in precious metals during economic policy uncertainties. The results are helpful for portfolio managers, institutional investors, and policymakers for the strategic allocation of their funds during monetary and fiscal policy uncertainties. Highlights: The study examines spillovers among policy uncertainties (Monetary and Fiscal), precious metals, and equity markets to investigate whether precious metals and equities are immune to monetary and fiscal policy uncertainties? The empirical results reveal that the overall spillover among the system variables is weak. The frequency-based results reveal that cross-spillovers between policy uncertainties and equity are mostly driven by shorter-horizons. It appears that precious metals are relatively more immune to the shocks from policy uncertainties than equity markets, thereby suggesting safe investment opportunities in precious metals during economic policy uncertainties.